SPECIFIC FEATURES OF VOCAL TELEVISION SHOWS IN MODERN POP MUSIC CULTURE - Tilovova, Shaxlo (Research Focus International Scientific Journal, 2026)
This article provides a broad and in-depth analysis of vocal television shows as an important phenomenon in modern popular music culture. Special attention is paid to their artistic-dramaturgical and social characteristics. The study examines the interaction of vocal performance and visual components, the competitive structure of television formats, and their role in intercultural communication. Vocal television shows are evaluated not only as entertainment projects but also as an important platform for developing, popularizing, and professionally promoting vocal art in modern mass media.